IAAF World High Jump Centre Cologne
Informationen über die Sportstätten, Trainingsmöglichkeiten und Serviceleistungen des internationalen Hochsprung-Trainingszentrums der IAAF in Köln. All coaches there have gained experience over several years in top level sport (incl. Olympic Games, World and European Championships), are available during the whole year and are fluent English speakers.